THE READINESS OF FUTURE COMPUTER SCIENCE TEACHERS TO FORM FUNCTIONAL LITERACY OF STUDENTS - Salgozha, И.Т.; Kassekeyeva, А.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
At present, functional literacy of students is the actual result of training. In this regard, the article deals with the issue of training of pedagogical personnel, ready and able to form functional literacy of students. The content of the concept of functional literacy is revealed in the article, the components of functional literacy are presented, and the way of their formation. The basis of functional literacy is laid at school. Functional literacy is the ability of a person to use all acquired knowledge, skills and abilities to solve the widest range of life tasks in various spheres of activity, communication and social relations. It is studied what competences the future teacher needs to master in order to prepare the student for such activities.